2023
DOI: 10.3390/plants12040820
|View full text |Cite
|
Sign up to set email alerts
|

3′-Demethoxy-6-O-Demethylisoguaiacin and Norisoguaiacin Nematocidal Lignans from Artemisia cina against Haemonchus contortus Infective Larvae

Abstract: Artemisia cina is a plant used in traditional Chinese medicine as a remedy for parasitic diseases. This study describes the isolation and chemical characterization of anthelmintic compounds of A. cina against Haemonchus contortus infective larvae (L3) through lethal testing. Previously, three extracts—n-hexane (HexAc), ethyl acetate (EtOAc) and methanol (MeOAc)—were evaluated at concentrations of 4 to 0.5 mg/mL, resulting in the HexAc extract with the greatest effect of 76.6% mortality of the larvae at 4 mg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…These compounds are responsible for a wide range of biological activities, including hepatoprotective, neuroprotective, antidepressant, cytotoxic, antitumor, digestion-stimulating and antiparasitic effects [10]. The n- hexane ( n -HE) extract of Artemisia cina has been documented for its anthelmintic activity against H. contortus , targeting eggs and L 3 infective larvae [8], transitional larvae L 3 -L 4 [4], and naturally infected periparturient goats [3]. Those activities are attributed to the presence of two lignans, 3′-Demethoxy-6-O-Demethylisoguaiacin and norisoguaiacin [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These compounds are responsible for a wide range of biological activities, including hepatoprotective, neuroprotective, antidepressant, cytotoxic, antitumor, digestion-stimulating and antiparasitic effects [10]. The n- hexane ( n -HE) extract of Artemisia cina has been documented for its anthelmintic activity against H. contortus , targeting eggs and L 3 infective larvae [8], transitional larvae L 3 -L 4 [4], and naturally infected periparturient goats [3]. Those activities are attributed to the presence of two lignans, 3′-Demethoxy-6-O-Demethylisoguaiacin and norisoguaiacin [8].…”
Section: Discussionmentioning
confidence: 99%
“…The n- hexane ( n -HE) extract of Artemisia cina has been documented for its anthelmintic activity against H. contortus , targeting eggs and L 3 infective larvae [8], transitional larvae L 3 -L 4 [4], and naturally infected periparturient goats [3]. Those activities are attributed to the presence of two lignans, 3′-Demethoxy-6-O-Demethylisoguaiacin and norisoguaiacin [8]. However, the low yield percentage of the n -HE and the lignans make it challenging to use for formulating or creating A. cina -based pharmaceutical preparations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bio-guided assays showed that the molecules responsible for the effect are 3′-demethoxy-6-O-demethylisoguaiacin and norisoguaiacin separated and isolated from an n -hexane extract of A. cina . The compounds showed 100% mortality against infective larvae of H. contortus 14 .…”
Section: Introductionmentioning
confidence: 99%